Tsunami detection by GPS-derived ionospheric total electron content - Mahesh N. Shrivastava (Nature Portfolio, 2021)
Abstract To unravel the relationship between earthquake and tsunami using ionospheric total electron content (TEC) changes, we analyzed two Chilean tsunamigenic subduction earthquakes: the 2014 Pisagua Mw 8.1 and the 2015 Illapel Mw 8.3. During the Pisagua earthquake, the TEC changes were detected at the GPS sites located to the north and south of the earthquake epicenter, whereas during the Illapel earthquake, we registered the changes only in the northward direction. Tide-gauge sites mimicked the propagation direction of tsunami waves similar to the TEC change pattern during both earthquakes. The TEC changes were represented by three signals. The initial weaker signal correlated well with Acoustic Rayleigh wave (AWRayleigh), while the following stronger perturbation was interpreted to be caused by Acoustic Gravity wave (AGWepi) and Internal Gravity wave (IGWtsuna) induced by earthquakes and subsequent tsunamis respectively. Inevitably, TEC changes can be utilized to evaluate earthquake occurrence and tsunami propagation within a framework of multi-parameter early warning systems.